ANALISIS MODAL KERJA PADA UD MAK DELPI LUBUK TUKKO KABUPATEN TAPANULI TENGAH - Risma Manullang; Safriadi Pohan; Rifka Hadia Lubis (Journal of Management and Social Sciences, 2022)
Working capital is all of the current assets that are used in the company's daily operations, such as advance purchases of raw materials, payment of wages/salaries for employees, laborers, and so on, where the funds that have been issued are returned to enter the company in a not too long period of time. a long time in through the company's sales results. This study aims to describe the working capital turnover of UD. Mak Delpi and to explain the profitability level of UD. Mom Delpi. The research method used is descriptive method with analysis of working capital turnover ratios (ratio of cash turnover, accounts receivable turnover, inventory turnover). The results of the analysis show that UD's working capital turnover. Mak Delpi Lubuk Tukko in 2019-2021 based on the cash turnover ratio and accounts receivable turnover ratio is considered good or effective, and based on the inventory turnover ratio it is so slow that it is considered ineffective.